TESTING FOR ANTIBACTERIAL ACTIVITY OF FRUIT SKIN ETHANOL EXTRACT DUKU (Lansium domesticum Corr) AGAINST BACTERIA Salmonella Typhi - Wulandari, Suci (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2024)
Salmonella typhimurium bacteria is the cause of typhoid fever. One of the herbal plants that can be used as an antibacterial drug is duku fruit peel (Lansium domesticum Corr). Phytochemical tests were carried out on duku fruit peel extract which was soaked in 96% ethanol solvent. The aim of this test is to identify secondary metabolites found in duku fruit skin. There are alkaloids, flavonoids, saponins, tannins and triterpenoids in the ethanol extract of duku fruit peel. This study involved four treatment groups with extract concentrations of 25 percent, 50 percent, and 75 percent, along with a positive control (chloramphenicol) and a negative control (distilled water). With inhibition zone diameters of 10.22 mm, 11.94 mm, and 13 mm, the ethanol extract of duku fruit peel showed antibacterial activity against Salmonella enterica bacteria. The results of univariate data analysis showed that the ethanol extract of duku fruit peel showed antibacterial activity at 25%, 50% and 75%. The results of univariate data analysis showed that the ethanol extract of duku fruit peel showed antibacterial activity against Salmonella typhi bacteria. In addition, the bacterial concentration increases with the width of the inhibition zone.